Conventional Rapid Latex Agglutination in Estimation of von Willebrand Factor: Method Revisited and Potential Clinical Applications - Mahat, Marianor; Abdullah, Wan Zaidah; Che Hussin, Che Maraina (Hindawi Publishing Corporation, 2014)
Measurement of von Willebrand factor antigen (VWF:Ag) levels is usually performed in a specialised laboratory which limits its application in routine clinical practice. So far, no commercial rapid test kit is available for VWF:Ag estimation. This paper discusses the technical aspect of latex agglutinationmethod which was established to suit the purpose of estimating vonWillebrand factor (VWF) levels in the plasma sample. The latex agglutination test can be performed qualitatively and semiquantitatively. Reproducibility, stability, linearity, limit of detection, interference, and method comparison studies were conducted to evaluate the performance of this test. Semiquantitative latex agglutination test was strongly correlated with the reference immunoturbidimetric assay (Spearman’s rho = 0.946,